The hidden mechanisms in political education: On the relation between school structure and knowledge on the example of the “base-concept” power - Brandmayr, Michael (Momentum Quarterly, 2015)
This paper contributes to the debate on “critical political education”. It centers the term “Hidden Curriculum” which points out the hidden mechanism of socialization within the process of schooling, where schools transmit certain values, norms and political adjustments “on the backstage” (Zinnecker 1978). The first part of this paper suggests a new formulation of the term, referring to critics that have been made in the historical debate. The second part demonstrates the relevance of this term for the field of political education. This starts with the appraisal that mechanisms described with the term have been noticed very little in concepts of political education, and as a result, the social context of school as learners’ common habitats is noticed too little. It shall be shown that on the one hand, school structures experiences to make some experiences more likely to happen; on the other hand, it is more likely that this experience will be interpreted in a certain way as an effect of social selection which favors the middle-classes’ worldviews. On the example of power as a “base-concept” of political education it will be argued that the claim for an ideological balance regarding content and interpretation may not be converted.